2008
DOI: 10.1073/pnas.0801991105
|View full text |Cite|
|
Sign up to set email alerts
|

Indo-European and Asian origins for Chilean and Pacific chickens revealed by mtDNA

Abstract: European chickens were introduced into the American continents by the Spanish after their arrival in the 15th century. However, there is ongoing debate as to the presence of pre-Columbian chickens among Amerindians in South America, particularly in relation to Chilean breeds such as the Araucana and Passion Fowl. To understand the origin of these populations, we have generated partial mitochondrial DNA control region sequences from 41 native Chilean specimens and compared them with a previously generated datab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

11
147
1
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(160 citation statements)
references
References 34 publications
11
147
1
1
Order By: Relevance
“…Unguja and Pemba game birds were both distributed in Liu's clade D and clade E. Oka et al (2007) and Gongora et al (2008) found Indian fighting birds in haplogroups that have been associated with Liu's clade D and fighting birds from Western Asia and Japan in Liu's clade E (Liu et al, 2006). Cockfighting was among the traditional sports in the Tanzanian islands of Unguja and Pemba, introduced by Austronesians in 945 -946 AD, as reported by Walsh (2006;.…”
Section: Discussionmentioning
confidence: 70%
“…Unguja and Pemba game birds were both distributed in Liu's clade D and clade E. Oka et al (2007) and Gongora et al (2008) found Indian fighting birds in haplogroups that have been associated with Liu's clade D and fighting birds from Western Asia and Japan in Liu's clade E (Liu et al, 2006). Cockfighting was among the traditional sports in the Tanzanian islands of Unguja and Pemba, introduced by Austronesians in 945 -946 AD, as reported by Walsh (2006;.…”
Section: Discussionmentioning
confidence: 70%
“…[17,18]; expansion of bovid herds throughout the Fertile Crescent (8500-9500 BP) [18,19]; and bovid introduction to Europe (5000-9000 BP) [17]. (b) First host jump from humans to avian hosts, with dashed lines representing the arrival of poultry in America (400 BP) [20]; the expansion of flocks in North America (140 BP) [21,22]; and the first factory farms (90 BP) [21]. …”
Section: Discussionmentioning
confidence: 99%
“…The earliest archaeological evidence of domestic chicken in Africa dates back to between 1300 BC and 1400 AD (Gifford-Gonzales and Hanotte, 2011). The origin of South American village chicken remains unclear with their eventual presence on the continent before the arrival of Europeans still the subject of debate (Storey et al, 2007;Gongora et al, 2008). Village chickens are typically considered as free-range panmictic birds (Dana et al, 2010a).…”
Section: Introductionmentioning
confidence: 99%